2005
DOI: 10.1186/1897-4287-3-2-81
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Familial Gastric Cancer and Chordoma in the Same Family

Abstract: Gastric cancers are the second most common malignancy in the world and represent a major burden to all societies even though the incidence of disease is decreasing in the industrialized world. The aetiology of the disease is complex and is believed to be primarily due to environmental factors but a small proportion of cases are recognised as being associated with genetic factors. Two inherited forms of stomach cancer have been identified, one which is associated with familial clusterings of stomach cancer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…No studies have been published regarding chordoma complications in patients with genetically confirmed Lynch syndrome, although Weber W et al reported a possible chordoma complication of Lynch syndrome, where it had not been genetically determined to be Lynch syndrome [ 16 ]. Lynch syndrome is an autosomal dominant cancer predisposition syndrome caused by a germline mutation in one of the following four MMR genes: MLH1, MSH2, MSH6, or PMS2 [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…No studies have been published regarding chordoma complications in patients with genetically confirmed Lynch syndrome, although Weber W et al reported a possible chordoma complication of Lynch syndrome, where it had not been genetically determined to be Lynch syndrome [ 16 ]. Lynch syndrome is an autosomal dominant cancer predisposition syndrome caused by a germline mutation in one of the following four MMR genes: MLH1, MSH2, MSH6, or PMS2 [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%